2011
DOI: 10.1186/1746-1596-6-100
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MK-1 and RegIV and its clinicopathological significances in the benign and malignant lesions of gallbladder

Abstract: BackgroundTo study the expression of MK-1 and RegⅣ and to detect their pathological significances in benign and malignant lesions of gallbladder.MethodsThe expression of MK-1 and RegⅣ was detected by immunohistochemical method in paraffin-embedded sections of surgical resected specimens from gallbladder adenocarcinoma (n = 108), peritumoral tissues (n = 46), adenomatous polyp (n = 15), and chronic cholecystitis (n = 35).ResultsThe positive rate of MK-1 or RegⅣ expression was significantly higher in gallbladder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 15 publications
(15 reference statements)
1
13
0
Order By: Relevance
“…Reg4, which was isolated from a cDNA library of ulcerative colitis (UC) tissues by Hartupee et al (3), is the most recently identified member of the Reg family. It has been reported that Reg4 was markedly overexpressed in several gastrointestinal types of cancer including gastric, colorectal and pancreatic cancer (4)(5)(6)(7)(8). In CRC, Oue et al (9) reported that Reg4 expression was associated with histologic grade and metastasis and high serum Reg4 concentrations were found in patients with liver metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Reg4, which was isolated from a cDNA library of ulcerative colitis (UC) tissues by Hartupee et al (3), is the most recently identified member of the Reg family. It has been reported that Reg4 was markedly overexpressed in several gastrointestinal types of cancer including gastric, colorectal and pancreatic cancer (4)(5)(6)(7)(8). In CRC, Oue et al (9) reported that Reg4 expression was associated with histologic grade and metastasis and high serum Reg4 concentrations were found in patients with liver metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…ERM proteins bind actin and, by means of their N-terminal domains, simultaneously the PIP2 located at the plasma membrane (Niggli, V et al 2008, Gilmore and Burridge 1996Isenberg and Niggli 1998, Nakamura et al 1999, Eberle et al 1990, Dobos et al 1992, Apgar 1995, Gachet et al 1997, Gratacap et al 1998. Once activated, Ezrin, commonly localized in the cytoplasm in its inactive form, moves and tethers actin to the cortical membrane, thus promoting cytoskeleton reorganization and subsequent cell morphology alterations (Dard et al 2004;Zhu et al 2007;Di Cristofano et al 2010;Yang et al 2012;Zhao et al 2011;Tan and Yang 2010). Beside phosphorylation, activation of ERM proteins also occurs after interaction with PIP2 (Gilmore and Burridge 1996, Hirao et al 1996, Legg and Isacke 1998, Nakamura et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Cell proliferation in CG is also regulated by a novel member of the Kr€ uppel C2H2-type zinc finger protein family, zinc finger X-chromosomal protein, which promotes growth, but also migration, of CG cells (Tan et al 2013). Cell proliferation of CG cells is induced by the morphogen, hepatocyte growth factor/HGF (Li et al 1998;Yang et al 2012), whereby the cancer cells express the HGF receptor, c-Met (Sasaki et al 2012). In CG, c-Met is immunohistochemically localized in the cell membrane (Sanada et al 2010).…”
Section: Factors Involved In Growth and Cell Cycle Regulationmentioning
confidence: 97%